Proposing a Practical Method for Conceptual Design Process in New Product Development: Medical Glasses as a Case Study - Amir Mirzadeh Phirouzabadi (International Journal of Informatics and Communication Technology (IJ-ICT), 2014)
Nowadays,improving the quality of products, reducing cost and meeting customer’srequirements are necessary to shorten the time of new product development(NPD). NPD is used to describe the complete process of bringing a new product to market and conceptual design process(CDP) is at its early stage and has mostly changed from passive respond toaggressive one. Thus, this study proposed a practical method for CDP in NPDthrough three phases as Converting customers’ requirements to product specifications,Generating and selecting of concepts and Testing and finalizing the concepts byusing some different management-engineering techniques. Firstly, this papertried to prioritize customer’s requirements related to product by AHP (AnalyticHierarchy Process) and convert them to engineering parameters of TRIZ (Theoryof Inventive Problem Solving) in order to define the inventive principals.Next, based on QFD (Quality Function Deployment), we measured the weight valuesof inventive principals. Finally, as FMEA (Failure Mode and Effect Analysis)can analyze the weight values and reduce the sequential risk, then finalconceptual design was generated. At the end, a medical glasses was used as acase study of innovative design to validate the method and explain how thestrategies of this research for CDP.